Identification and Analysis of the Blood lncRNA Signature for Liver Cirrhosis and Hepatocellular Carcinoma - Xia, Qi; Shu, Zheyue; Ye, Ting; Zhang, Min (Frontiers in Genetics, 2020)
As one of the most common malignant tumors, hepatocellular carcinoma (HCC) is the fifth major cause of cancer-associated mortality worldwide. In 90% cases, HCC develops in the context of liver cirrhosis and chronic hepatitis B virus (HBV) infection is an important etiology for cirrhosis and HCC, accounting for 53% of all HCC cases. To understand the underlying mechanisms of the dynamic chain reactions from normal to HBV infection, from HBV infection to liver cirrhosis, from liver cirrhosis to HCC, we analyzed the blood lncRNA expression profiles from 38 healthy control samples, 45 chronic hepatitis B patients, 46 liver cirrhosis patients and 46 HCC patients. Advanced machine learning methods including Monte-Carlo feature selection, Incremental Feature Selection (IFS) and Support Vector Machine (SVM) were applied to discover the signature associated with HCC progression and construct the prediction model. 171 key HCC progression-associated lncRNAs were identified and their overall accuracy was 0.823 as evaluated with leave-one-out cross validation (LOOCV). The accuracies of the lncRNA signature for healthy control, chronic hepatitis B, liver cirrhosis and HCC were 0.895, 0.711, 0.870 and 0.826, respectively. The 171 lncRNA signature is not only useful for early detection and intervention of HCC, but also helpful for understanding the multi-stage tumorigenic processes of HCC.